Identifying a male clinical cutoff on the Eating Disorder Examination‐Questionnaire (EDE‐Q). Issue 12 (27th November 2018) - Schaefer, Lauren M.; Smith, Kathryn E.; Leonard, Rachel; Wetterneck, Chad; Smith, Brad; Farrell, Nicholas; Riemann, Bradley C.; Frederick, David A.; Schaumberg, Katherine; Klump, Kelly L.; Anderson, Drew A.; Thompson, J. Kevin
Abstract: Objective: Evidence suggests that eating disorders (EDs) may be under‐detected in males. Commonly used measures of EDs such as the Eating Disorder Examination‐Questionnaire (EDE‐Q) were initially developed within female samples, raising concern regarding the extent to which these instruments may be appropriate for detecting EDs in males. The current study used receiver operating characteristic curve analysis to (a) examine the accuracy of the EDE‐Q global score in correctly classifying males with and without clinically significant ED pathology, and (b) establish the optimal EDE‐Q global clinical cutoff for males. Method: Participants were a clinical sample of 245 male ED patients and a control sample of 205 male undergraduates. Results: Eating Disorder Examination‐Questionnaire global scores demonstrated moderate‐high accuracy in predicting ED status (area under the curve = 0.85, 95% CI: 0.82–0.89). The optimal cutoff of 1.68 yielded a sensitivity of 0.77 and specificity of 0.77. Discussion: Overall, results provide preliminary support for the discriminant validity of EDE‐Q scores among males. However, concerns remain regarding the measure's ability to comprehensively assess domains of disordered eating most relevant to males. Therefore, careful attention to the possibility for measurement bias and continued evaluation of the scale in males is encouraged.